2020
DOI: 10.1371/journal.pone.0240717
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Bordetella pertussis disease in hospitalized children

Abstract: Introduction Despite a resurgence of disease, risk factors for pertussis in children in low and middleincome countries are poorly understood. This study aimed to investigate risk factors for pertussis disease in African children hospitalized with severe LRTI. Methods A prospective study of children hospitalized with severe LRTI in Cape Town, South Africa was conducted over a one-year period. Nasopharyngeal and induced sputum samples from child and nasopharyngeal sample from caregiver were tested for Bordetella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…The risk of HCoV infection was not associated with HIV status. This contrasts with other pathogens in published studies in South Africa in which the risk of respiratory pathogens such as RSV was shown to be associated with HIV exposure among children [20,29]. It is not fully clear why this association with coronavirus as shown in our reported results is missing.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The risk of HCoV infection was not associated with HIV status. This contrasts with other pathogens in published studies in South Africa in which the risk of respiratory pathogens such as RSV was shown to be associated with HIV exposure among children [20,29]. It is not fully clear why this association with coronavirus as shown in our reported results is missing.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to RSV and other respiratory viruses in which children younger than 6 months got severe infection, vaccines have been targeted for maternal vaccination to protect them [29]. This finding is consistent with the literature in which older children who got coronavirus were reported to be less likely to get severe respiratory illness [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Assessing factors associated with B. pertussis incidence, children <5 years of age who did not receive the full schedule of pertussis vaccine for age were more likely to be infected with B. pertussis than were vaccinated children. Similarly, other studies in South Africa showed that risk for pertussis and risk for hospitalization caused by pertussis decreased when persons were vaccinated ( 9 , 14 ).…”
Section: Discussionmentioning
confidence: 57%
“…The overall household cumulative infection risk was (9,14). Data on duration of PCR-positive B. pertussis infection among persons are limited.…”
Section: Household Cumulative Infection Riskmentioning
confidence: 99%